DETERMINACIÓN DE LA POTENCIA DEL COMPONENTE SARAMPIÓN DE LA VACUNA DE VIRUS VIVO DE SARAMPIÓN Y RUBÉOLA USP UTILIZADA EN LA JORNADA DE VACUNACIÓN 2005 - A. Bermúdez-Forero; M. Mercado-Reyes; P. Tavera; G. Rey-Benito (Universitas Scientiarum)
Quality of vaccines is an imperative factor to guarantee success and effectiveness of vaccination programs.This study was done to verify if bivalent vaccine (Live attenuated measles and rubella vaccine U.S.P.)used during the National Vaccination Campaign in 2005, maintained the specifications of 1000 DICT 50.Six vials per vaccine lot were used. Samples were obtained from different regions of the country. Protocoldescribed in the Manual of Laboratory Methods for testing vaccines used in the WHO Expanded Programmeof Immunization was used. Titer vaccine in TCID 50 was calculated by the Reed-Muench method and anhypothesis test for mean TCID 50 obtained in the titration was performed to determine if it was greater orequal to the one reported by manufacturer. Additionally, a correlation analysis was done calculatinginterlot agreement correlation index (δc). Titers obtained in potency tests showed very low agreementbetween different lots, as well as between titers obtained from vials of the same vaccine lot. This variationin titers can occur due to factors like maintenance of cold chain during storage, transportation or distributionof vaccine through different vaccination points in the country. The technique used to determine thepotency of vaccines, was suitable, and can be used by the National Regulatory Authorities, to perform teststo determine quality of vaccines.